The activation energy and antibacterial investigation of spherical Fe3O4 nanoparticles prepared by Crocus sativus (Saffron) flowers - Rajendrachari, Shashanka; Ceylan, Kevser Betül; Ceylan, Kevser Betül (Biointerface Research Applied Chemistry, 2020)
We proposed a simple and environmental-friendly method to prepare magnetite nanoparticles and their application as antibacterial material. We successfully prepared Fe3O4 nanoparticles using Crocus Sativus (Saffron) flowers followed by calcination at 400 degrees C for 15 minutes. The UV-Visible spectroscopy was used to study the bandgap energy of the prepared Fe3O4 nanoparticles and the value was found to be 3.23 eV. The scanning electron microscopy (SEM) was used to study the structure and morphology and X-ray diffraction was used to study the phase and crystallite size of the magnetite nanoparticles. The percentage weight loss, the enthalpy change and activation energy of Fe3O4 nanoparticles were calculated by using the thermogravimetric (TG) and differential thermal analysis (DTA) respectively. The DTA curve at a heating rate of 6, 8 and 10 degrees C/min shows endothermic peaks at 586, 594 and 600 degrees C respectively. The activation energy of Fe3O4 nanoparticles was calculated by the Kissinger method and was found to be 8.09 kJ/moles. The antibacterial activity of Fe3O4 nanoparticles was carried out against 3 gram-positive and 3 gram-negative bacteria by using a minimum inhibition concentration (MIC) assay method and they showed excellent antibacterial activity against gram-negative bacterial strains only.
Keywords: Antibacterial Activity; Fe3o4 Nanoparticles; Crocus Sativus; Saffron Flower Extract; Activation Energy